Impacts of participatory forest management on forest conditions: Evidences from Gebradima Forest, southwest Ethiopia. (16th November 2016) - Tadesse, Solomon; Woldetsadik, Muluneh; Senbeta, Feyera
ABSTRACT: This study examines a participatory forest management program and its impacts on forest conditions in Gebradima Forest, southwest Ethiopia. Vegetation data were collected from both participatory forest management (PFM) and nonparticipatory forest management (non-PFM) forest blocks. A total of 54 plots (27 from each forest block) measuring 20 m × 20 m were employed to collect species composition and structural data. Results indicated that a total of 51 different woody plant species (49 at PFM and 43 at non-PFM blocks), representing 31 families were recorded, with 41 species were shared for both forest sites. Species diversity and evenness were higher in the forest with PFM (H´ = 3.29, E = .85) compared to the forest without PFM (H´ = 2.97, E = .79). The overall mean values of tree/shrub and seedling density per hectare, diameter class (≤ 20 cm) were also significantly ( p  < .05) higher in PFM forest than non-PFM forests. However, no significant variations were observed in sapling density per hectare and basal area between the two studied forest blocks. It can be concluded that PFM had a positive effect on forest conditions compared with a similar forest without PFM. Hence, it is important to scaling up PFM in neighboring forests.